2005
DOI: 10.1002/app.22707
|View full text |Cite
|
Sign up to set email alerts
|

Thermal decomposition behavior of γ‐irradiated poly(vinyl acetate)/poly(methyl methacrylate) miscible blends

Abstract: Miscible polymer blends based on various ratios of poly(vinyl acetate) (PVAc) and poly(methyl methacrylate) (PMMA) were prepared in film form by the solution casting technique using benzene as a common solvent. The thermal decomposition behavior of these blends and their individual homopolymers before and after γ‐irradiation at various doses (50–250 kGy) was investigated. The thermogravimetric analysis technique was utilized to determine the temperatures at which the maximum value of the rate of reaction (Tmax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…Mass losses between 300°C and 450°C and 550°C and 650°C come from decomposition of the binder. Polyvinyl acetate is reported to decompose thermally in two steps . The first leads to loss of acetic acid and the second results from decomposition of the resulting carbon chain.…”
Section: Resultsmentioning
confidence: 99%
“…Mass losses between 300°C and 450°C and 550°C and 650°C come from decomposition of the binder. Polyvinyl acetate is reported to decompose thermally in two steps . The first leads to loss of acetic acid and the second results from decomposition of the resulting carbon chain.…”
Section: Resultsmentioning
confidence: 99%
“…This behavior indicated that thermal decomposition of these polymers passed through multiple stages, depending on the state of decomposition and not on the components. 19 As it can be seen, in the Figures 1 and 3(a) and (b) the third and fourth degradation regions were overlapped for Resin 1, and second and third degradation regions for Resin 3, which led to 2 simultaneously occurring process degradation with a total weight loss of 35.75% and 19.10%, respectively.…”
Section: Thermal Analysismentioning
confidence: 85%
“…Note that the rate of the thermal decomposition reaction of all polymers, whether before or after cirradiation, showed more than one maximum with increasing temperature. This behavior indicates that the thermal decomposition of these polymers passes through multiple stages, depending on the state of decomposition and not on the components [49].…”
Section: Thermal Analysismentioning
confidence: 96%